Ethnopedagogical Features Of Directing Future Primary Teachers To Scientific Activities - Inoyatova, Zulfiya Hamdamovna; Urinboyeva, Umida (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the content, significance and methodological foundations of the process of directing future primary school teachers to scientific activity. In the formation of scientific activity, the main goal is to develop scientific thinking, problem-solving, analysis and scientific conclusion competencies in students. In this direction, the methodological significance of the ethnopedagogical approach in enriching scientific activity in content is analyzed.